On the Ultra-Precision Fabrication of Damage-Free Optical KDP Components: Mechanisms and Problems. Issue 4 (4th July 2019) - Hou, Ning; Zhang, Liangchi; Zhang, Yong; Zhang, Feihu
Abstract: Potassium dihydrogen phosphate (KDP) crystals have excellent optical properties such as high nonlinear conversion efficiency, superior photoelectric and piezoelectric properties, transparency in a wide range of optical spectra, and good optical homogeneity. Therefore, KDP crystals have been used in many advanced fields, such as in the laser ignition facilities as large aperture crystals for optical switching and frequency conversion. However, extensive trials in the past decades showed that a KDP crystal is an extremely difficult-to-handle material for its high sensitivity to external stresses and environmental conditions, such as contact stresses, temperature variation and moisture invasion. It is also a soft material yet easy to fracture. A critical challenge is that it is unclear about the underlying physics of the damages which have been frequently observed after the ultra-precision surfacing of an optical KDP lens. As a result, when it is used in a Pockels photoelectric switch in a high-density laser system, for instance, its optical performance (e.g., its laser-induced damage threshold) is unexpectedly low. These have hindered significantly the development of high performance laser systems. This paper aims to provide a comprehensive review on the critical integrity issues of KDP components and their characterization methods, from the points of view of microstructure, micro/nano-mechanics, deformation mechanisms and laser-induced damage associated with the most commonly used surfacing technology––ultra-precision machining.